STRUKTUR RANTAI PASOK (SUPPLY CHAIN), KELEMBAGAAN DAN KLASTER INDUSTRI KOMODITAS CABAI : SEBUAH TINJAUAN LITERATUR - Analia, Devi (AGRIPITA JOURNAL, 2017)
Red chili is one of the horticultural vegetables cultivated by farmers. Chili commodity prices tend to fluctuate so that it takes the management of the supply chain to be more efficient. The design of red chili commodity supply chain includes upstream and downstream management. Supply chain concept is a concept that saw the entire activity of the company is an integrated part. In this case the integration of companies in the upstream in providing raw materials and integration at the downstream in the distribution and marketing of products. SCM is a set of approaches that are applied to suppliers, entrepreneurs, warehouses and other storage areas efficiently to products produced and distributed with the right quality, location and the right time to reduce costs and satisfy customer needs. This paper is a review of literature related to the supply chain of red pepper. In this paper the focus was discussed on the upstream (upstream) and downstream (downstream) commodity suintegration supply chain that contained chili pepper prices rise towering is also included with the physical condition of chili that was not fresh anymore. Plus the market is not well ordered, thus affecting the marketing activities of red pepper. In addition to the institutional role of the supply chain for farmers is necessary to ensure the balance of the price of pepper at both farmers and end-consumer level. Last to maintain price stability and availability of red chili the farmer and the final consumer is to create and design an industrial cluster of red chillies.